Mapping programmes for mental health promotion in Singapore: A scoping review - P.V. AshaRani; Xin Er Ong; Zakir Karuvetil; Christine S.M. Chen; Lim Ther; Lee Cheng; Mythily Subramaniam; Timothy Liu (PLoS ONE, 2026)
Mental health disorders are on the rise globally, with policies promoting programmes that aim to enhance mental wellbeing across various population domains. This scoping review aims to examine the literature to identify and map the mental health programmes in Singapore, while identifying critical knowledge gaps and scope for future systematic reviews. A systematic search was conducted across multiple databases including Medline, PsycINFO, CINAHL, OpenGrey and ProQuest, complemented by hand and bibliography searches. Articles published from 2000 onwards in English language were included. Independent parallel reviews were conducted by multiple reviewer pairs. Data was extracted into standardised, pre-piloted templates that incorporated the Template for Intervention Description and Replication (TIDieR) checklist. One hundred and six studies were included in the review, demonstrating diverse programmes targeting different age groups, with particular focus on older adults in hospital and community settings. The programmes addressed mental health outcomes in individuals with mental disorders, physical conditions, neurodevelopmental and learning disabilities, and among healthy individuals. Implemented by trained care teams or multidisciplinary professionals, these programmes generally showed positive outcomes. However, significant gaps were identified in the literature regarding user experiences, with minimal focus on implementation barriers and enablers. Notably, there was limited evidence of successful community-level implementation beyond the experimental phase, raising questions about programme sustainability and real-world effectiveness. Critical gaps were also identified in youth-specific suicide prevention programmes, despite suicide being a leading cause of death among youths, and programmes targeting the impact of built environment on mental health outcomes and workplace wellbeing. These areas represent important opportunities for future research and intervention development in Singapore’s mental health landscape. Singapore has developed an active research network over the past decade to design and implement programmes aimed at improving mental health across different populations and settings. However, stronger collaborative approaches between academics and policymakers are needed to better utilise research findings and understand which programmes add value to the public health domain. Future research should focus on implementation science, long-term sustainability, and cost-effectiveness of these programmes in real-world settings.